Volarian Game: Engaging EFL Learners’ Vocabulary Learning During the Covid-19 Outbreak - Hayatul Rizqiana (STKIP PGRI Trenggalek, 2021)
This research aims at developing a Volarian game to engage EFL learners to learn vocabulary during the Covid-19 outbreak. This research was conducted with Research and Development (R&D) and tested in Class Action Research (CAR). Then, the researcher distributes pre-motivation and post-motivation questionnaires to know the students’ engagement in learning vocabulary during study at home before and after using Volarian. In the pre-motivation questionnaire total score indicated a point of 1036. The number 1036 is in the strongly disagree and disagree score range which means that student engagement in learning vocabulary during study at home is low. However, in a post-motivation questionnaire result, a total score indicated a point of 1853. The number 1853 is in the agree and strongly agree score range which means that after the student using Volarian can engage them to learn vocabulary during study at home. Accordingly, based on the recapitulation of pre-motivation and post-motivation questionnaires show that the results of field-testing by using CAR (Class Action Research) method prove that there is an engagement of students in learning vocabulary during distance learning before and after using Volarian.